The active problem solving of patients dependent on home parenteral nutrition: A qualitative analysis. (August 2018) - Ennis, Liam; Ablett, Joanne; Taylor, Michael; Lal, Simon
Summary: Background & aims: People with chronic, type 3, intestinal failure often require long-term home parenteral nutrition (HPN). People receiving HPN have frequent interactions with their healthcare, due to the need for close monitoring and due to recurrent hospital admissions. Individuals' responses to, and interactions with, their health care service provides are poorly described. We conducted a service evaluation to explore people's experiences of HPN-related healthcare interactions in order to identify how service providers can best meet the individualised needs of patients. Methods: We interviewed ten people receiving HPN. The participants were asked about their healthcare interactions related to HPN. The data were analysed using a qualitative research method known as interpretive phenomenological analysis. This analytical approach is concerned with the meaning that people ascribe to particular events, in this case their HPN-related healthcare interactions. Results: The participants in this study described a range of psychosocial problems related to their HPN healthcare interactions, including reliance, risk and restrictions. Participants' solutions to these problems included adaptation of their routine, self-guardianship and passivity. Sometimes, these solutions generated secondary problems of their own, including concerns with resource use, negative healthcare interactions and conflicts of responsibility. A range of contextual factors influenced how participants interpreted their healthcare interactions and the solutions available to them. These contextual factors included continuity of healthcare professionals, the attitude of staff, and information and knowledge about HPN. Conclusions: By attending to the individual meaning ascribed to healthcare events, and the contextual factors that surround these events, we have been able to better understand the decisions made by patients dependent on HPN. This suggests that healthcare professionals may also better understand their patients' decision making by attending to the individual meaning that patients ascribe to healthcare events and to contextual factors. We propose a model to describe the process of problem -> resolution -> problem in which participants are actively engaged.